SENAM HAMIL EFEKTIF MENURUNKAN TINGKAT KECEMASAN PADA IBU HAMIL TRIMESTER III - Dyka Aidina; Yulia Netri (STKIP Subang, 2026)
Pregnant women often feel more anxious due to the effects of physical changes. This anxiety is caused by increased levels of the hormone progesterone. Exercise is one way to manage anxiety and stress. Research indicates that prenatal exercise can alleviate anxiety during pregnancy. Objective: This study investigates the effectiveness of prenatal exercise in reducing anxiety among pregnant women in the third trimester at the Rostian Midwife Clinic in Padang. Method: This study employed a quasi-experimental design. A group of pregnant women in the third trimester underwent pre- and post-intervention assessments. Univariate and bivariate analyses were used to determine the effects of prenatal exercise on anxiety levels among pregnant women in the third trimester. Results: Before the intervention, moderate anxiety levels were 60%, and severe anxiety was 36.67%. After the intervention, moderate anxiety was 56.66%, mild anxiety was 40%, and severe anxiety was 3.33%. All of the above findings indicate that exercising during pregnancy can significantly reduce anxiety in the third trimester. The results of the analysis yielded a p-value of 0.000, and since this p-value is smaller than the significance level (α = 5% or 0.05), this indicates a significant effect of prenatal exercise on anxiety levels in pregnant women in the third trimester. Conclusion: There was a decrease in anxiety levels both before and after the intervention; prenatal exercise has a significant effect on reducing anxiety levels in pregnant women in the third trimester